2016
DOI: 10.1016/j.nano.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Dual-therapy with αvβ3-targeted Sn2 lipase-labile fumagillin-prodrug nanoparticles and zoledronic acid in the Vx2 rabbit tumor model

Abstract: Fumagillin, an unstable anti-angiogenesis mycotoxin, was synthesized into a stable lipase-labile prodrug and incorporated into integrin-targeted lipid-encapsulated nanoparticles (αvβ3-Fum-PD NP). Dual anti-angiogenic therapy combining αvβ3-Fum-PD NP with zoledronic acid (ZA), a long-acting osteoclast inhibitor with proposed anti-angiogenic effects, was evaluated. In vitro, αvβ3-Fum-PD NP reduced (p<0.05) endothelial cell viability and tube formation without impacting macrophage viability. ZA suppressed (p<0.05… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…We have previously shown that αvβ3-NP bind to the tumor endothelium in vivo 54 . We next assessed the ability of αvβ3-rhodamine NP to bind myeloid cells in vivo .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…We have previously shown that αvβ3-NP bind to the tumor endothelium in vivo 54 . We next assessed the ability of αvβ3-rhodamine NP to bind myeloid cells in vivo .…”
Section: Resultsmentioning
confidence: 97%
“…However, the integrin αvβ3-targeting peptidomimetic binds with high affinity to the ligand-binding domain exposed with activated integrins, avoiding binding to inactivated αvβ3 integrin on quiescent cells. We have previously shown that integrin αvβ3-targeting to the neovasculature can be used to specifically deliver cargoes with αvβ3-PFC NP in pathologic animal models of cardiovascular, inflammatory disease and cancer 54 , 84 , 85 . The cMYC-MAX pathway is upregulated in tumor neovasculature, which also expresses the activated integrin 86 .…”
Section: Discussionmentioning
confidence: 99%
“…Fum-PD is ineffective when co-incubated with activated macrophages in culture, but it is effective against vascular tubule formation in vitro. 24, 57 Dxtl-PD can suppress macrophage inflammatory cytokine release in vitro and in vivo, as well as being anti-angiogenic 30 ( Supporting Information: S1 ). In the present study, α v β 3 -Dxtl-PD micelles, in addition to the anti-angiogenic anti-inflammatory effects elicited by targeting neoendothelial cells similar to α v β 3 -Fum-PD micelles, they likely bound phagocytic cells, possibly the M2 phenotype macrophages increased in antigen-induced asthma.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, studies on bisphosphonates used alone or in combination with anticancer drugs or physicochemical methods for the treatment of tumorigenesis are promising fields of research, and highlight possibility of developing novel therapeutic strategies (70)(71)(72)(73)(74).…”
Section: Prospective Use Of Tams For Anticancer Therapymentioning
confidence: 99%